Polyamine Antagonist Therapies Inhibit Neuroblastoma Initiation and Progression - Evageliou, Nicholas F.; Haber, Michelle; Vu, Annette; Laetsch, Theodore W.; Murray, Jayne; Gamble, Laura D.; Cheng, Ngan Ching; Liu, Kangning; Reese, Megan; Corrigan, Kelly A.; Ziegler, David S.; Webber, Hannah; et al. (Clinical cancer research, 2016)
Purpose: Deregulated MYC drives oncogenesis in many tissues yet direct pharmacologic inhibition has proven difficult. MYC coordinately regulates polyamine homeostasis as these essential cations support MYC functions, and drugs that antagonize polyamine sufficiency have synthetic-lethal interactions with MYC. Neuroblastoma is a lethal tumor in which the MYC homologue MYCN, and ODC1, the rate-limiting enzyme in polyamine synthesis, are frequently deregulated so we tested optimized polyamine depletion regimens for activity against neuroblastoma. Experimental Design: We used complementary transgenic and xenograft-bearing neuroblastoma models to assess polyamine antagonists. We investigated difluoromethylornithine (DFMO; an inhibitor of Odc, the rate-limiting enzyme in polyamine synthesis), SAM486 (an inhibitor of Amd1, the second rate-limiting enzyme), and celecoxib (an inducer of Sat1 and polyamine catabolism) in both the preemptive setting and in the treatment of established tumors. In vitro assays were performed to identify mechanisms of activity. Results: An optimized polyamine antagonist regimen using DFMO and SAM486 to inhibit both rate-limiting enzymes in polyamine synthesis potently blocked neuroblastoma initiation in transgenic mice, underscoring the requirement for polyamines in MYC-driven oncogenesis. Furthermore, the combination of DFMO with celecoxib was found to be highly active, alone, and combined with numerous chemotherapy regimens, in regressing established tumors in both models, including tumors harboring highest risk genetic lesions such as MYCN amplification, ALK mutation, and TP53 mutation with multidrug resistance. Conclusions: Given the broad preclinical activity demonstrated by polyamine antagonist regimens across diverse in vivo models, clinical investigation of such approaches in neuroblastoma and potentially other MYC-driven tumors is warranted. Clin Cancer Res; 22(17); 4391–404. ©2016 AACR.